Peningkatan Kapasitas Kelompoktani Melalui Inovasi Teknologi Pembuatan Pupuk Organik Di Kecamatan Janapria Kabupaten Lombok Tengah - Sudjatmiko, Dwi Praptomo; Siddik, Muhamad; Anwar, Anwar; Dipokusumo, Bambang; Fadli, Fadli (Universitas Mataram, 2024)
During 2013-2019, rice production and cattle population in West Nusa Tenggara Province increased, however, rice productivity tended to decrease. One of the reasons for this decline in rice productivity is the excessive and continuous use of chemical fertilizers, which causes the soil structure to harden. Therefore, it is necessary to develop the use of non-chemical fertilizers or organic fertilizers whose raw materials come from cow dung which is often found in the field. Apart from that, animal feed, especially cows, is actually available around the community, namely in the form of forage from plants. However, management of forage for livestock has not been carried out by many farmers. Based on these problems, this community service activity aims to increase the capacity of farmer-livestock groups to be able to apply technology for making organic fertilizer and feed management. This community service activity was carried out in Saba Village, Janapria District, Central Lombok Regency, where there is quite a lot of agricultural waste potential available. Implementation of activities includes: outreach, Focus Group Discussion (FGD), training, and practice in making organic fertilizer and managing animal feed. The target of the activity was 30 members of the farmer-livestock group in Janapria District. The output of the activity is increasing farmers' knowledge, skills and attitudes in organic fertilizer production technology; as well as the production of solid organic fertilizer (compost), liquid organic fertilizer and animal feed from agricultural waste. Output in the academic aspect is in the form of writing in journals or seminar proceedings. The evaluation results using statistical methods with paired sample t tests in this activity showed that there was a significant increase in farmer-breeder behavior after participating in training activities in making organic fertilizer and making feed. Some farmer-breeders have implemented the results of the training and feel that there are savings in farming costs by using organic fertilizer that they make themselves